SNARE-Driven, 25-Millisecond Vesicle Fusion In Vitro - Liu, Tingting (Biophysical Society, 2005)
Docking and fusion of single proteoliposomes reconstituted with full-length v-SNAREs (synaptobrevin) into planar lipid bilayers containing binary t-SNAREs (anchored syntaxin associated with SNAP25) was observed in real time by wide-field fluorescence microscopy. This enabled separate measurement of the docking rate k(dock) and the unimolecular fusion rate k(fus). On low t-SNARE-density bilayers at 37°C, docking is efficient: k(dock) = 2.2 × 10(7) M(−1) s(−1), ∼40% of the estimated diffusion limited rate. Full vesicle fusion is observed as a prompt increase in fluorescence intensity from labeled lipids, immediately followed by outward radial diffusion (D(lipid) = 0.6 μm(2) s(−1)); ∼80% of the docked vesicles fuse promptly as a homogeneous subpopulation with k(fus) = 40 ± 15 s(−1) (τ(fus) = 25 ms). This is 10(3)–10(4) times faster than previous in vitro fusion assays. Complete lipid mixing occurs in <15 ms. Both the v-SNARE and the t-SNARE are necessary for efficient docking and fast fusion, but Ca(2+) is not. Docking and fusion were quantitatively similar on syntaxin-only bilayers lacking SNAP25. At present, in vitro fusion driven by SNARE complexes alone remains ∼40 times slower than the fastest, submillisecond presynaptic vesicle population response.